Latitudinal gradient of biting midges in the genus Culicoides (Diptera: Ceratopogonidae) in Argentina and Bolivia - Veggiani Aybar, Cecilia A. (2015)
We provide the first records of 8 species of biting midges in the genus Culicoides (Diptera: Ceratopogonidae) in a wide latitudinal gradient of the Yungas Ecoregion in Argentina and the Chaco Ecoregion in Bolivia, including a map of their distribution, and an updated checklist of species in the study area. Additional locality records were obtained from published articles and from specimens collected in these and other ecoregions in both countries. Included are the first Argentinean records of Culicoides crescentis Wirth & Blanton and C. pampaensis Spinelli & Wirth from Salta Province; C. caridei Brèthes, C. crescentis, C. guttatus Coquillett, C. insignis Lutz, C. pampaensis, and C. venezuelensis Ortiz & Mirsa from Jujuy Province, and C. saltaensis Spinelli & Wirth and C. pampaensis from Tucumán Province. In addition, the first records of C. brasilianum Forattini, C. crescentis, and C. guttatus are provided from Bolivia.